Soil quality assessment based on soil organic matter pools under long‐term tillage systems and following tillage conversion in a semi‐humid region - Martinez, Juan Manuel (2020)
A field study was conducted to assess the long-term effects of no-tillage (NT) and conventional tillage (CT), and the short-term effects following tillage conversion -from CT to NT (NTn) and from NT to CT (CTn) on soil quality (SQ) indicators in a semi-humid climate. First, plots of a long-term tillage experiment on a Luvic Phaeozem initiated in 1986, were split into two subplots in 2012, yielding four treatments: NT, CT, NTn and CTn. In 2015, composite soil samples were collected from each treatment and from a natural site (Ref) at depths 0-5, 5-10, 10-20 and 0-20 cm. Several indicators were determined: soil organic carbon (SOC) and nitrogen (SON); particulate organic C (POM-C) and N (POM-N); potential N mineralization (PMN) and soil respiration (Rs). Moreover, bulk density was determined in long-term tillage systems. Different ratios between indicators were calculated, with emphasis on its function in the agroecosystem, i.e. functional indicators. Significant differences in SOC, SON and PMN were found between CT and NT at most depths. In contrast, three years after tillage conversion, only a part of the SQ indicators studied were modified mainly at the 0-10 cm depth. The functional indicators showed differences between tillage systems in the long-term and after short-term tillage conversion depending on the depth; however, the PMN/SON ratio demonstrated differences at all depths. Under these conditions, this ratio -related to easily mineralizable N fraction- proved to be a promising indicator for assessing SQ under contrasting tillage systems regardless of the sampling depth.